The History of Articulators: Early Attempts to Reproduce Mandibular Movement, Part II - Edgar N. Starcke, DDS (Blackwell Synergy, 2000)
IN 1889, RICHMOND S. HAYES (Fig 1) of East Bloomfield, NY received a patent for an articulator that was the first to incorporate a fixed descending condylar path.1 Hayes introduced this new feature nearly 50 years after the Daniel T. Evens articulator pioneered a provision for the lateral and protrusive movements of the mandible.2